Python machine learning cookbook : over 100 recipes to progress from smart data analytics to deep learning using real-world datasets - Ciaburro, Giuseppe; Joshi, Prateek (Packt Publishing, 2019)
With this book, you will learn how to perform various machine learning tasks in different environments. You'll use a wide variety of machine learning algorithms using Python to solve real-world problems. By the end of the book, you will learn to implement most used machine learning algorithms using complex datasets and optimized techniques.
Previous edition published: 2016.
Keywords: Python (Computer program language); Machine learning.; elektronické knihy; electronic books